Studi Kelayakan Bisnis Kuliner Berbasis Budaya Batak Toba di Wilayah Balige - Chairiza Azmi; Chitra Annisa Ramadhaningtyas; Aditiya Pratama Daryana (Fakultas Ekonomi dan Bisnis Islam, 2025)
This research aims to assess the feasibility of establishing and developing a Batak Toba culture-based culinary business in the Balige region, Toba Regency, as a form of strengthening local creative economy initiatives in synergy with regional cultural assets. The study is grounded in the underutilization of traditional cuisine as a symbol of local economic identity, despite the Danau Toba region being designated as a National Super Priority Tourism Destination by the central government. A descriptive qualitative approach was employed, incorporating field observations, in-depth interviews with five traditional culinary business owners, and consumer surveys distributed to 50 respondents. Data analysis was structured around five key aspects of business feasibility: market potential, technical and operational capacity, management and human resources, legal and licensing status, and financial viability. This was further complemented by a SWOT analysis. The results reveal high consumer interest in Batak Toba traditional food, particularly for authentic and culturally significant dishes. Technically, raw material availability is abundant, yet production facilities and hygiene infrastructure remain limited. Most business owners do not keep financial records and lack formal operational structures. Legal compliance is also low, with many lacking Business Identification Numbers (NIB) or hygiene certifications. Nevertheless, financial simulations indicate that the business is economically feasible, with a projected payback period of approximately four months and a promising level of net profit. In conclusion, the Batak Toba culinary business in Balige is considered viable for development, provided it is supported by continuous assistance in business management, quality standardization, and legal facilitation. Integrating cultural heritage with modern business strategies is key to positioning traditional cuisine as a central component of the region’s cultural tourism ecosystem.